A Morte do Escritor (Brasileiro)?The Death of the (Brazilian) Writer? (PerCursos, 2009)
Este artigo apresenta, a partir da leitura de Álvaro Simões Junior e Luiz Carlos Simon, um panorama do escritor brasileiro na passagem do século XIX para o XX por um lado, e a produção intelectualcontemporânea pautada na literatura brasileira moderna por outro. Analisa as relações entre o ato de escrever e o produto da escritura, partindo da materialidade de dois gêneros: literatura e jornalismo que tem como ponto de intersecção um outro: a crônica.Palavras-Chave: Autor. Intelectual. Literatura. Jornalismo. Escritor. Abstract: This article prsents, from reading Alvaro Simões and Luiz Simo's works, a view of the Brazilianauthor in the turning of the XIX century to XX century on the other hand, and the intellectual contemporary production ruled in the Brazilian modern Literature for another one. It anlyses the relatiins between the act ofwriting and the product of the scripture, coming to a focus the materiality in two kinds of genre: Literatura and Journalism, which a intersection point is the chronicle. Keywords: Author. Intellectual. Literature. Journalism. Writer.